Determination Of Polyphenol Levels And Antioxidant Activity Extract Combination Instant Powder Preparation Katuk Leaf (Sauropus androgynus (L.) Merr.) And Cacacao Beans (Theobroma cacao L.) - Youstiana Dwi Rusita (Journal of Science and Technology Research for Pharmacy, 2022)
Natural immunomodulators are obtained from herbal plants with natural antioxidant content.The content of polyphenol compounds as natural antioxidants in katuk leaves and cocoa beansis utilized in the form of instant powder preparations.This study aimed to determine the levels of polyphenols and the antioxidant activity of instantpowder combination of katuk leaves and cocoa beans.Material dan Methods : this study used a quantitative descriptive method with test parametersincluding organoleptic, moisture content, ash content, polyphenol qualitative, polyphenolcontent and antioxidant activity.The results of the instant powder moisture content test were 1.71 ± 0.04%; 1.68 ± 0.03%; and1.59 ± 0.03%. The results of the instant powder ash content test were 1.16 ± 0.03%; 1.18 ±0.04%; and 1.11 ± 0.03%. The positive instant powder qualitative test results containedpolyphenols as indicated by the formation of blackish-brown color. Polyphenol levels in instantpowder were 43.83 ± 1.76 mg GAE/g; 34.40 ± 0.71 mg GAE/g; and 29.50 ± 0.76 mg GAE/g.The instant powder is classified as a medium antioxidant category with an IC50 value of 119.25ppm respectively; 129.25 ppm; and 146,40 ppm.The Conclusion Formula 1 is a formula that has a large polyphenol content and strongantioxidant activity.